The Role of E27-K31 and E56-K10 Salt-Bridge Pairs in the Unfolding Mechanism of the B1 Domain of Protein G - Tony Ibnu Sumaryada; Kania Nur Sawitri; Setyanto Tri Wahyudi (Universitas Gadjah Mada, 2018)
Molecular dynamics simulations of the B1 fragment of protein G (56 residues) have been performed at 325, 350, 375, 400, 450 and 500 K for 10 ns. An analysis of its structural and energetic parameters has indicated that the unfolding process of the GB1 protein begins at 900 ps of a 500-K simulation. The unfolding process is initiated when hydrogen bonds in the hydrophobic core region are broken; it continues with the α-helix transformation into coils and turns and ends with the destruction of the β-hairpins. These unfolding events are consistent with the hybrid model of the protein folding/unfolding mechanism, which is a compromise between the hydrophobic core collapse model and the zipper model. Salt-bridge pairs were found to play an important role in the unfolding process by maintaining the integrity of the tertiary structure of the protein. The breaking (or disappearance) of the salt-bridge pairs E27–K31 (in the α-helix) and E56–K10 (connecting β4 and β1) has resulted in the destruction of secondary structures and indicates the beginning of the unfolding process. Our results also suggest that the unfolding process in this simulation was not a complete denaturation of the protein because some β-hairpins remained